1986
DOI: 10.1021/jf00070a040
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-metal absorption by soybean on sewage sludge treated soil

Abstract: Studies were conducted to determine absorption of Cd, Ni, Cu, and Zn by soybean [Glycine max (L.) Merr.] grown on Enon soil treated with sewage sludge. The sludge rates were 0, 40, 80, and 120 Mg ha™1. Bragg and Ransom varieties of soybeans were grown in pots to maturity. Cadmium concentration in seeds was found to be 0.08 and 0.20 gg g™1 for the control and 120 Mg ha™1 sludge treatments, respectively. Bragg and Ransom showed significant difference in the absorption of Cd and Cu. There were significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…This confirms the results of increased accumulation of Cu, Zn (Reddy and Dunn, 1986;Reddy et al, 1989;Heckman et al, 1987), Mo (McBride et al, 2000;O'Connor et al, 2001) in soil and tissues of soybean grown on biosolid amended soils. According to Heckman et al (1987) the soybean tissue concentrations of Zn, Cd, Cu and Ni exhibited significant linear increase with increase in rate of sludge application from 0 to 112 Mg/hac.…”
Section: Discussionsupporting
confidence: 87%
“…This confirms the results of increased accumulation of Cu, Zn (Reddy and Dunn, 1986;Reddy et al, 1989;Heckman et al, 1987), Mo (McBride et al, 2000;O'Connor et al, 2001) in soil and tissues of soybean grown on biosolid amended soils. According to Heckman et al (1987) the soybean tissue concentrations of Zn, Cd, Cu and Ni exhibited significant linear increase with increase in rate of sludge application from 0 to 112 Mg/hac.…”
Section: Discussionsupporting
confidence: 87%
“…Cd accumulation in the edible parts is thus likely to be controlled by the general translocation properties of leaves, stems, and roots via the xylem and phloem. Genetic variability for Cd uptake has been reported in soybean [2,22,23,25,[50][51][52]. The seed Cd concentration of certain genotypes was consistently low under all field and soil conditions.…”
Section: Genetic Control Of CD Accumulationmentioning
confidence: 99%
“…Morishita et al 12 found that Cd levels in brown rice grains ranged from 2.1 to 27.0 ppb among 28 japonica varieties and from 4.1 to 55.5 ppb among 23 indica varieties under normal soil conditions. Reddy and Dunn 13 reported significant differences in seed grain Cd levels between two soybean varieties grown on sewage sludge amended soil.…”
Section: Introductionmentioning
confidence: 99%